Directors remuneration and firm value of Malaysian listed firms - Mohd Waliuddin, Bin Mohd Razali; Muhammad Faizal, Abdul Manas; Janifer, Lunyai; Dyg Haszelinna, Abg Ali; Irma Yazreen, Md Yusoff (2018)
Directors remuneration has attracted considerable interest among the scholars and the financial analyst as it seen to be a main reason of good firm performance. This paper sought to examines the director‘s remuneration and the firm value in Malaysia. The data and the materials were collected from the Bursa Malaysia website and the Eikon Thomson Reuters. Data of the director remuneration, CEO duality and board size were obtained from the annual report where the other variable such as the firm value, firm size, leverage were collected from the Eikon Thomson Reuters database. The samples of this paper using 602 firms from different industries from 2014 to 2016 period. Regression analysis shows that non-cash directors remuneration has stronger significant positive relationship with firm value rather than cash remuneration. It proves that the remunerations received by directors can motivate them to perform better for the firm. The analysis also shows board size and firm age positive significantly related with the firm value. Further, the potential limitation of using firm value as the only dependent variable may not provide more meaningful insight of the impact of other components of the performance measure such as excess in value, growth and other performance measure. Thus future study may use these variables for future study.